Bead optimization in long fiber reinforced polymer structures: Consideration of anisotropic material properties resulting from the manufacturing process. (November 2020) - Revfi, Sven; Mikus, Marvin; Behdinan, Kamran; Albers, Albert
Highlights: Improved design of load-bearing, beaded components by manufacturing-based optimization. Stiffness-optimized bead cross section depends on the manufacturing process. Automated, simulation-based design support tool for beaded long fiber reinforced polymers. Abstract: This contribution investigates the influence of anisotropic, linear-elastic material properties resulting from the manufacturing process of long fiber reinforced polymer structures on the stiffness-optimized design of beaded plates. A workflow for the coupling of manufacturing and structural simulations in an automated optimization loop controlled by a genetic algorithm is presented. First, the influence of the local, anisotropic material properties resulting from the manufacturing process on the stiffness-optimized bead cross section is studied. By additionally considering a strength constraint in the optimization, application-oriented bead geometries for real-world scenarios can be generated with the developed methodology. The results of the manufacturing-based design process differed from the bead geometries calculated with isotropic material properties, which were used for validation. These findings support the product developer when designing stiffness-optimized bead geometries in long fiber reinforced polymer structures.